Non-coding RNAs in Natural Killer/T-Cell Lymphoma - Mei, Mei; Zhang, Mingzhi (Frontiers in Oncology, 2019)
Natural killer/T-cell lymphoma (NKTCL) is a rare and aggressive subtype of non-Hodgkin's lymphoma that is associated with a poor outcome. Noncoding RNAs (ncRNAs), which account for 98% of human RNAs, lack the function of encoding proteins but instead have the important function of regulating gene expression, including transcription, translation, RNA splicing, editing, and turnover. However, the roles and mechanisms of aberrantly expressed noncoding RNAs in NKTCL are not fully clear. Aberrant expressions of miRNAs affect the PI3K/AKT signaling pathways (miR-21, miR-155, miR-150, miR-142, miR-494), NF-ĸB (miR-146a, miR-155) and cell cycle signaling pathways to regulate cell function. Moreover, EBV-encoded miRNAs and EBV oncoprotein LMP-1, can regulate the expression of cellular genes that induce invasion, metastasis, cell cycle progression and cellular transformation. In addition, NKTCL-associated lncRNA ZFAS1 regulate certain pathways and MALAT1 act as a predictive marker. This review article provides an overview of ncRNAs associated with NKTCL, summarizes the function of significantly differentially expressed hotspot noncoding RNAs that contribute to the pathogenesis, diagnoses, treatment and prognosis of NKTCL and discusses the relevance of these noncoding RNAs to clinical practice.